(untitled) (Itinera, 2024)
In this essay, I intend to investigate some of the aspects of the resurgence of habit at the dawn of the twentieth century by touching upon a series of paradigmatic texts of the modernist canon and by investigating their debts to and consonances with the contemporary philosophies of habit. My thesis is that during those decades – seen as a mere chapter in the longer history of modernity – the philosophical and literary theme of habit served not only as a way to understand and represent the ordinary dimension of life, but also as a means to develop an idea of human subjectivity that could mediate between the centrifugal and the centripetal tendencies that permeated the competing ideologies of the time. The crisis of subjectivity that characterized modernism and which has often been simplistically represented as a disintegration of the subject into irredeemably broken fragments, should rather be seen as the development of a dialectical idea of a “minor subject”, that is, an open, dynamic, multilayered subjectivity still endowed by a certain malleable consistency. Both modernist literature and its philosophical counterparts found in the “minor subject” (here in the sense of “subject matter”) of habit, the opportunity to investigate and represent the porosity between activity and passivity, volition and determinism, individual identity and social structures, that characterize this idea of subjectivity. I focus on three different representative – though not exhaustive – facets of the issue. In the first section, relying on Virginia Woolf’s work, I highlight how some of the narrative techniques developed by Modernist writers can be seen as an attempt to give a plastic representation to the blurred boundaries of subjectivity as captured in the everyday existence of their characters. I then connect these innovations to the theory of habit of Samuel Butler, whom Woolf identified as one of the harbingers of modernity. In the second section I focus on Marcel Proust to discuss how modernist writers proved to be able to combine two opposed views of habit: on the one hand, the view of habit as purely mechanical and leading to inauthentic life; on the other, the idea of habit as essential to the human being’s potential for self-perfecting and creativity. The third section is dedicated to addiction, seen as a form of habit in which the subject is radically torn between opposite forces. Following insights from Sigmund Freud’s Beyond the Pleasure Principle, I interpret Italo Svevo’s Zeno’s Conscience as a meditation on how such a torn subjectivity manifests the essential incompleteness of the human subject and life’s insuppressible nostalgia for the inorganic. Virginia Woolf’s blurred boundaries, Marcel Proust’s ambiguous authenticity, and Italo Svevo’s split selfhood are three interconnected facets of the modernists’ interest in the “minor subject” of habit. Investigating the interaction between the philosophical and the literary discourses on habit at the dawn of the twentieth century can contribute to a more nuanced reconstruction of a pivotal moment in the history of thought but also to the contemporary philosophical debate. Almost exactly one century later, the renewed interest in the theme of habit mirrors a situation in part similar to what characterized the ideological landscape of the time, as now too it is concerned with the attempt to reimagine a “minor subject” that mediates between the postmodern pulverization of identity and the temptation of reaffirming anachronistic forms of strong subjectivities.